Improving efficiency of air purifiers from wood dust to reduce industrial load on environment (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The object of the study is cyclone cleaners with active working bodies. These cleaners are designed to separate wood particles from the air stream. The transition zone between the cleaner body and the active working body is considered, in which the axisymmetric flow changes both direction and speed. The purpose of this study is to develop a method for determining the radial and vertical components of the air flow velocity vector field in this zone.The research was carried out by the method of mathematical modeling. The following simplifications were used: streamlines were approximated by ellipse arcs; the flow of an ideal fluid was considered. The dust-air flow in the investigated zone of the cleaner is considered as a flow of an ideal fluid divided into elementary infinitely thin curved tubes. Since the flow in each of them is constant, it is possible to determine the modulus of the flow rate at a given point of the region, taking into account the variable cross-sectional area of such a tube.Analytical dependences of the vertical and radial components of the vector field of the air flow velocity in the transition zone between the housing and the active working body of the air cleaner were obtained.
Keywords: wood particle; air purifier; rotor; flow line; vector field; air-flow velocity